A quality control study on a lubricant production - Deguito, Therese Sheila (College of Engineering, 1999)
A statistical control study was done on one of the Philippine-based oi companies. This company, company A, was formed when two big U.S. companies entered a joint venture. From here different petroleum produces like gasoline lubricants and greases, were manufactured under company A's mane in the Philippines, the formulations coming from both mother companies. The Pandacan plant was chosen since this was where lubricants and greases were manufactured for Philippine consumption. The researchers chose lubricant 1 since it's a fast moving lubricant, meaning it's the most in demand lubricant they make and it's the product with the most profit. What the researchers did first was tour the manufacturing plant while the different processes were being explained. Next, the researchers interviewed the Lubricants Production Manager and gathered enough data to analyze the quality control that the company uses. In analyzing, they were able to apply different techniques like Ishikawa diagram, Pareto chart, failure mode effects and analysis chart and control charts. While analyzing the process the researchers were able to come up with two possible problem areas: blending and filling and packaging process. However, due to lubricant 1's high demand, of which workers are familiar to the amount of each ingredient to put, therefore this lubricant has zero reblends. For the filling and packaging process, the researchers recommend that the company should not only rely on the suppliers certificate of conformance but also make random sampling on the delivered containers to assure quality. The researchers also suggest that the company keep track of each supplier's performance.